P403 Adherence to vaccination recommendations in patients with Inflammatory Bowel Disease: a long way for improving. (27th May 2021) - Ferreiro Iglesias, R; Hernández Camba, A; Saldaña, R; Rodríguez-Lago, I; Zabana, Y; Barreiro-de Acosta, M
Abstract: Background: Despite the existence of specific recommendations, patients with inflammatory bowel disease (IBD) have shown low immunization rates. The aim of this study was to evaluate the adherence to vaccination recommendations by physicians to their IBD patients. Methods: An online anonymous survey was sent to 8000 patients from a national patient association (ACCU-Spain). Three invitations were sent between October-December 2020. Questions were jointly designed by ACCU and GETECCU. Potential reasons for vaccination compliance were evaluated and analysed for different vaccines: age, gender, type of IBD, type of healthcare and treatments. Descriptive analyses and logistic regression were performed to identify factors associated with adherence to vaccination recommendations. Results: 1302 patients with IBD responded to the survey (mean age 43 years [SD 12], 72% women). Forty percent of patients had ulcerative colitis, 58% Crohn's disease and 2% indeterminate colitis. 91% of patients were treated in public facilities, 5% in a private setting and 4% in both. 41% of patients were treated with 5ASA, 35% with azathioprine/methotrexate, 50% with biologics and 8% with corticosteroids. Although [IRL1] [YZ2] physicians recommended vaccination, 45% were not adherent to papilloma virus vaccine, 18% to pneumococcus, 18% to hepatitis B vaccine, 16% to influenza and 12% to tetanus. The main reason for non-compliance to physician recommendation was considering that is not necessary (Table 1). Some factors associated to vaccine compliance are shown in Table 2. Conclusion: Non-adherence to vaccination recommendations in IBD patients is frequent. Patients with immunosuppressive therapy show less compliance to the vaccination recommendations. The importance and benefits of vaccination needs to be explained to improve the adherence in IBD patients.